Analisis Risiko Keselamatan dan Kesehatan Kerja pada Pengelolaan Linen Instalasi Laundry di Rumah Sakit Umum GMIM Bethesda Kota Tomohon - Elshaday Natalia Moningka; Paul A. T. Kawatu; Jeini E. Nelwan (Pusat Riset dan Inovasi Nasional, 2025)
Occupational Safety and Health (OSH) is an important element in every workplace, especially in hospitals. One of the important areas in a hospital is the laundry unit/installation, which is responsible for managing both medical and non-medical linen. This research aims to identify hazards present in the laundry unit, conduct a risk assessment, and provide K3 risk control measures for the management of laundry linen at RSU Bethesda Tomohon. The type of research used is qualitative with in-depth interview and observation methods. The research was conducted from March to May 2025. The informants in this study consisted of 4 people, including the head of the laundry installation, laundry staff in the wash and sewing sections, and members of the K3 Team. The research findings revealed a total of 42 occupational safety and health risks spread across 7 linen management processes, with 6 risks categorized as low, 33 risks as moderate, and 3 risks as high. The highest-risk hazards are found in the stages of transportation, sorting, and washing of linen that involve direct contact with contaminated infectious linen. The main hazard is biological exposure to pathogenic microorganisms that can cause serious infections.